2014
DOI: 10.1001/jamadermatol.2013.10225
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Microscopy–Guided Laser Ablation for Superficial and Early Nodular Basal Cell Carcinoma

Abstract: Importance Laser ablation is a rapid and minimally invasive approach for the treatment of superficial skin cancers, but efficacy and reliability vary owing to lack of histologic margin control. High-resolution reflectance confocal microscopy (RCM) may offer a means for examining margins directly on the patient. Observations We report successful elimination of superficial and early nodular basal cell carcinoma (BCC) in 2 cases-, using RCM imaging to guide Er-:YAG laser ablation. Three-dimensional (3-D) mappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…Our work, together with other studies in vivo (Tannous et al , 2003, Nori et al 2004; Scope et al, 2010; Guitera et al 2012; Pan et al, 2013; Chen et al 2014), suggests the potential possibility of peri-operative RCM imaging of superficial and early nodular BCCs to guide noninvasive diagnosis, pre-treatment detection of tumor margins, less invasive (ablative) treatment and post-treatment monitoring, directly on the patient. The ablation may be combined with other approaches such as debulking of tumor for enhancing the efficacy of treatment.…”
Section: To the Editorsupporting
confidence: 64%
See 1 more Smart Citation
“…Our work, together with other studies in vivo (Tannous et al , 2003, Nori et al 2004; Scope et al, 2010; Guitera et al 2012; Pan et al, 2013; Chen et al 2014), suggests the potential possibility of peri-operative RCM imaging of superficial and early nodular BCCs to guide noninvasive diagnosis, pre-treatment detection of tumor margins, less invasive (ablative) treatment and post-treatment monitoring, directly on the patient. The ablation may be combined with other approaches such as debulking of tumor for enhancing the efficacy of treatment.…”
Section: To the Editorsupporting
confidence: 64%
“…Preliminary studies in human skin ex vivo with acetic acid for nuclear contrast (Sierra et al , 2013) and in vivo with aluminum chloride (Chen et al , 2014) revealed feasibility of imaging in post-ablated tissue. However, the imaging was of variable quality.…”
Section: To the Editormentioning
confidence: 99%
“…These techniques can also identify spectroscopic molecular differences between tissue types, but weak autofluorescence can often require seconds of acquisition time per point. Real-time confocal microscopy, as a label-free modality, has been used to guide laser ablation of basal cell carcinoma and assess resected skin tumor and tissue specimens during Mohs surgeries, which replaces the time and expense of frequent histological processing of resected specimens (34). …”
Section: Point-of-procedures Platformsmentioning
confidence: 99%
“…Consequently, less invasive and less expensive nonsurgical alternative therapies are being increasingly developed. [11][12][13] Nonsurgical therapies can be particularly effective for minimally invasive removal of superficial and nodular BCCs, 14 which constitute about 40% (600,000 per year) of the total Mohs surgical cases. With such therapies, however, there is no tissue available for immediate pathological evaluation for the presence or clearance of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Although RCM has an inherently small field of view (FOV), usually limited to about 1 × 1 mm, larger areas can be imaged and the lateral margins of the tumor can be determined by the acquisition of video mosaics. 14,15,24 However, the penetration depth of RCM imaging is limited to 100 to 200 μm, which is not sufficient for estimating the deeper margins of BCCs. Therefore, OCT imaging, which has been proven to visualize the microanatomy of BCCs to depths of at least 1 mm, [40][41][42][43][44][45] is a complementary technology that can be used for this purpose.…”
Section: Introductionmentioning
confidence: 99%